Diarrhetic shellfish toxins production appears to be driven by photosynthesis and phosphate–revealed by different light-adapted strains of Prorocentrum lima complex and P. caipirignum - Chen, Heng; Huang, Kaixuan; Guan, Wanchun; Zhang, Hua; Liu, Shasha; Lu, Songhui (Frontiers in Marine Science, 2023)
Introduction Diarrhetic shellfish toxins (DST) harm shellfish aquaculture and endanger human health, and include well-known marine dinoflagellate-produced toxins such as okadaic acid (OA) and analogues, such as dinophysistoxin-1 (DTX-1). Toxin-producing species have different toxin profiles and contents, with unclear interactions, with the toxins hypothesized to be produced under stress conditions. Methods Five morphotypes of Prorocentrum lima complex, a well-studied DST-producing species with remarkable phylogenetic variability, were chosen and exposed to three distinct light conditions (photosynthetic active radiation, PAR; PAR+UVA; PAR+UVA and UVB) for 18 or 24 days. Results and discussion The studied morphotypes were classified as either light-sensitive (LS) or light-tolerant (LT) types based on their light responses and varying abilities to produce DTX-1 across three orders of magnitude (0.001-1 pg cell-1 d-1, abbreviated as LL, ML, and HL in order of rank). All toxin production rates (Rtox) initially increased and then decreased, with the first peaks varying between days 3 to 12. The results of earlier peaks in LL and ML and a linear correlation between Rtox values for OA and DTX-1 in HL indicated that the two compounds may be competitive. When light conditions initially altered, Rtox was either stagnant or negative under all light treatments in the LS cohort, and with UV addition in LT, which subsequently delayed the early peaks. The Rtox data for DTX-1 all demonstrated earlier and higher peaks with UVA addition in LL and ML. Likewise, their growth was facilitated following the addition of UVA light. Therefore, Rtox of pre-peaks is relevant to photosynthetic status and photoprotection ability. As decreasing Rtox data points corresponded closely with phosphate depletion, the phosphate consumption rate was calculated and shown to be linearly or exponentially associated with all downward Rtox. This study proposes a supply-demand link between photosynthetic products and phosphate with DST biosynthesis, inferring a likely competitive interaction between OA and DTX-1 production.